2022
DOI: 10.3389/fonc.2022.992348
|View full text |Cite
|
Sign up to set email alerts
|

Surgical clinical trials for HPV-positive oropharyngeal carcinoma

Abstract: The treatment of HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) continues to evolve as multiple ongoing and recently completed clinical trials investigate the role of surgery, radiation therapy, chemotherapy, and immunotherapy. Current trials are investigating transoral robotic surgery (TORS) in treatment de-escalation protocols in an effort to optimize quality of life, while maintaining historical survival rates. The advantage of TORS is its minimally invasive approach to primary resection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Because of the anatomical location of the primary tumour, especially if it is in the base of the tongue, surgical management has significant adverse consequences on physiological functions such as speech and swallowing 9 . However, in selected patients, surgical management may be indicated with removal of the primary tumour and lymph nodes by transoral laser surgery or robotic resection with neck dissection 10 . This is most suitable for the earliest stage tumours where the primary tumour can be removed with clear margins and there is minimal nodal spread.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the anatomical location of the primary tumour, especially if it is in the base of the tongue, surgical management has significant adverse consequences on physiological functions such as speech and swallowing 9 . However, in selected patients, surgical management may be indicated with removal of the primary tumour and lymph nodes by transoral laser surgery or robotic resection with neck dissection 10 . This is most suitable for the earliest stage tumours where the primary tumour can be removed with clear margins and there is minimal nodal spread.…”
Section: Managementmentioning
confidence: 99%
“…9 However, in selected patients, surgical management may be indicated with removal of the primary tumour and lymph nodes by transoral laser surgery or robotic resection with neck dissection. 10 This is most suitable for the earliest stage tumours where the primary tumour can be removed with clear margins and there is minimal nodal spread. However, in most cases adjuvant therapy with radiation or chemotherapy and radiation combined is necessary, and if chemoradiation is anticipated at the time of diagnosis then surgery is not indicated.…”
Section: Diagnosismentioning
confidence: 99%
“…Given this growing population of young and healthy patients who are presenting with often well-behaved tumors, our field is being driven toward de-escalating treatment for this population with the goal of maintaining excellent outcomes while improving treatment-related toxicity. Many trials have shown promise with significant de-escalation while preserving survival outcomes 4–6 . However, there remains a population of patients who ultimately fail even standard-of-care therapy, and there is a lack of consensus on how to categorize patient risk.…”
mentioning
confidence: 99%
“…Many trials have shown promise with significant de-escalation while preserving survival outcomes. [4][5][6] However, there remains a population of patients who ultimately fail even standard-of-care therapy, and there is a lack of consensus on how to categorize patient risk. As such, there is an ongoing need for improved patient stratification and surveillance methods.…”
mentioning
confidence: 99%